Cardiac Tamponade on the Edge. Issue 10 (22nd May 2015) - Krishnasamy, Kavita P.; Frazin, Leon J.; Kansal, Mayank
Mini‐Abstract Low‐pressure cardiac tamponade is an uncommon phenomenon in the spectrum of pericardial diseases. We describe a case of a 37‐year‐old man with recurring admissions for dyspnea whose clinical picture challenged the classic exhibition of cardiac tamponade.